Low pH treatment of starch industry effluent with bacteria from leaf debris for methane production. (7th February 2019) - Chaterjee, Pradip Kumar; Neogi, Shubhaneel; Saha, Shouvik; Jeon, Byong‐Hun; Dey, Apurba
Abstract: Cornstarch industry generates a huge amount of acidic effluent, that is, 5–11 M 3 /Mt grinding, with a high load of chemical oxygen demand, 6000–19000 mg/L. The acidic effluent requires neutralization making the treatment process expensive. Methanogenesis under the acidic environment (pH 5–5.5) can reduce the cost of operation as well as treatment time. This research focuses on the evaluation of the optimum condition of COD reduction and methane generation simultaneously from leaf debris sludge using Box–Behnken model. Three 1 L bioreactors were seeded with 5000–10000 mg/L inoculum and operated at different pH 4.0–7.0 for 72 hr up to 10 cycles. The production of methane was found maximum 2980 ml after treating the wastewater from the starch industry at pH 5.57 and 9612.9 mg biomass load at 62.4 hr. The high reduction rate of around 97% shows there is ample opportunity for further research on low pH treatment of waste along with recovery as methane. Practitioner points: The low pH tolerant methanogenic bacteria are promising and are isolable from various natural resources. The low pH tolerant methanogens was able to remove 97% COD from starch industry effluent at pH 5.57. The recovery of methane was 2980 ml from 9612 mg/L COD which is at per with present treatment system thus provides cost effective alternatives.